Cathodoluminescence and Raman Spectromicroscopy of Forsterite in Tagish Lake Meteorite: Implications for Astromineralogy. (22nd February 2016) - Gucsik, Arnold; Gyollai, Ildikó; Nishido, Hirotsugu; Ninagawa, Kiyotaka; Izawa, Matthew M. R.; Jäger, Cornelia; Ott, Ulrich; Simonia, Irakli; Bérczi, Szaniszló; Kayama, Masahiro
Abstract : The Tagish Lake meteorite is CI/CM2 chondrite, which fell by a fireball event in January 2000. This study emphasizes the cathodoluminescence (CL) and Raman spectroscopical properties of the Tagish Lake meteorite in order to classify the meteoritic forsterite and its relation to the crystallization processes in a parent body. The CL-zoning of Tagish Lake meteorite records the thermal history of chondrules and terrestrial weathering. Only the unweathered olivine is forsterite, which is CL-active. The variation of luminescence in chondrules of Tagish Lake meteorite implies chemical inhomogeneity due to low-grade thermal metamorphism. The blue emission center in forsterite due to crystal lattice defect is proposed as being caused by rapid cooling during the primary crystallization and relatively low-temperature thermal metamorphism on the parent body of Tagish Lake meteorite. This is in a good agreement with the micro-Raman spectroscopical data. A combination of cathodoluminescence and micro-Raman spectroscopies shows some potentials in study of the asteroidal processes of parent bodies in solar system.